Analisis Kepuasan Pasien BPJS Kesehatan terhadap Pelayanan Rawat Jalan di Rumah Sakit - Silfiatul Mukaromah; Selvia Juwita Swari; Ervina Rachmawati; Gandu Eko Julianto Suyoso (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The success of health services is related to the level of patient satisfaction. Hospitals are required to provide quality services in accordance with standards and targets. The purpose of this study was to analyze BPJS Kesehatan patient satisfaction with outpatient services at the hospital in terms of 5 dimensions of SERVQUAL using the literature review method. A total of 15 articles that met the inclusion and exclusion criteria were obtained from Google Scholar, Crossref, and Garuda Portal. The results of the review are reliability; patients are satisfied with the accuracy of the patient service process, but are not satisfied with the timeliness and service procedures. Responsiveness; patients are satisfied with the ability of officers to respond to patient requests, but are dissatisfied with the speed and responsiveness of officers in treating patients. assurance; patients are satisfied with the competence of officers as well as guarantees of security and safety provided, but patients are also dissatisfied with the competence and friendliness and courtesy of officers. Empathy; patients are satisfied with officers who do not discriminate and respect patients, but patients are not satisfied with officers who are not attentive. Tangibles; patients are satisfied with the cleanliness, tidiness, and comfort of the facility, but there are still patients who are dissatisfied with this.Keywords: service; quality; satisfactionABSTRAK Keberhasilan pelayanan kesehatan memliki keterkaitan dengan tingkat kepuasan pasien. Rumah sakit wajib menyelenggarakan pelayanan yang bermutu sesuai dengan standar dan sasaran. Tujuan studi ini adalah menganalisis kepuasan pasien BPJS Kesehatan terhadap pelayanan rawat jalan di rumah sakit ditinjau dari 5 dimensi SERVQUAL dengan metode literature review. Sebanyak 15 artikel yang memenuhi kriteria inklusi dan eksklusi diperoleh dari Google Scholar, Crossref, dan Portal Garuda. Hasil review yaitu reliability; pasien puas dengan kecermatan proses pelayanan pasien, namun tidak puas dengan ketepatan waktu dan prosedur pelayanan. Responsiveness; pasien puas dengan kesanggupan petugas dalam menanggapi permintaan pasien, namun tidak puas dengan kecepatan dan daya tanggap petugas dalam menangani pasien. Assurance; pasien puas dengan kompetensi petugas serta jaminan keamanan dan keselamatan yang diberikan, namun pasien juga tidak puas dengan kompetensi serta keramahan dan kesopanan petugas. Empathy; pasien puas dengan petugas yang tidak diskriminasi dan menghargai pasien, namun pasien tidak puas dengan petugas yang tidak perhatian. Tangible; pasien puas dengan kebersihan, kerapian, dan kenyamanan fasilitas, tapi masih terdapat pasien yang tidak puas dengan hal tersebut.Kata kunci: pelayanan; kualitas; kepuasan